Stripping Away the Soil: Plant Growth Promoting Microbiology Opportunities in Aquaponics - Bartelme, Ryan P.; Oyserman, Ben O.; Blom, Jesse E.; Sepulveda-Villet, Osvaldo J.; Newton, Ryan J. (Frontiers in Microbiology, 2018)
As the processes facilitated by plant growth promoting microorganisms (PGPMs) become better characterized, it is evident that PGPMs may be critical for successful sustainable agricultural practices. Microbes enrich plant growth through various mechanisms, such as enhancing resistance to disease and drought, producing beneficial molecules, and supplying nutrients and trace metals to the plant rhizosphere. Previous studies of PGPMs have focused primarily on soil-based crops. In contrast, aquaponics is a water-based agricultural system, in which production relies upon internal nutrient recycling to co-cultivate plants with fish. This arrangement has management benefits compared to soil-based agriculture, as system components may be designed to directly harness microbial processes that make nutrients bioavailable to plants in downstream components. However, aquaponic systems also present unique management challenges. Microbes may compete with plants for certain micronutrients, such as iron, which makes exogenous supplementation necessary, adding production cost and process complexity, and limiting profitability and system sustainability. Research on PGPMs in aquaponic systems currently lags behind traditional agricultural systems, however it is clear that certain parallels in nutrient use and plant-microbe interactions are retained from soil-based agricultural systems.